1998
DOI: 10.1007/s007050050398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bafilomycin Aff1 on Japanese encephalitis virus in C6/36 mosquito cells

Abstract: Involvement of intracellular acidic compartments in the early phase of Japanese encephalitis (JE) virus infection of C6/36 mosquito cells was examined by bafilomycin A1, a specific inhibitor of vacuolar type H(+)-ATPase (V-ATPase). Dose dependent reduction of viral envelope protein (E) produced into the infected culture fluid was observed by pretreating the cells with 0.25 to 1.0 microM bafilomycin A1. In synchronized infection, cell surface-bound virions were internalized immediately by heating at 31 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 25 publications
4
36
0
1
Order By: Relevance
“…It is established that all flaviviruses require acidification in the endosome for uncoating and release of the viral nucleic acid for replication (11,69). We confirmed that JEV entry in Neuro2a cells was acid dependent, as pretreatment of cells with 100 to 200 nM bafilomycin A1, a drug that is a potent inhibitor of the vacuolar ATPase and specifically prevents acidification of endosomal vesicles (70), led to about a 95% decrease in JEV infection in both Neuro2a and Vero cells (Fig.…”
Section: Jev Internalization Is Dynamin-2 Dependentsupporting
confidence: 76%
“…It is established that all flaviviruses require acidification in the endosome for uncoating and release of the viral nucleic acid for replication (11,69). We confirmed that JEV entry in Neuro2a cells was acid dependent, as pretreatment of cells with 100 to 200 nM bafilomycin A1, a drug that is a potent inhibitor of the vacuolar ATPase and specifically prevents acidification of endosomal vesicles (70), led to about a 95% decrease in JEV infection in both Neuro2a and Vero cells (Fig.…”
Section: Jev Internalization Is Dynamin-2 Dependentsupporting
confidence: 76%
“…4B) to 1 M, the GFP fluorescence began showing slight inhibition with increasing concentrations of BAF. BAF has been shown to affect the V-ATPases from a variety of insects at concentrations as low as 10 nM (21,35,54,55). These results agree with previous observations showing that lysosomotropic weak bases do not block the entry of virus RNA into insect cells (7,19) and further support the idea that a functional V-ATPase, and by extension endosome acidification and endocytosis, is not required for infection of cells by SV.…”
Section: Vol 85 2011 Role Of the Vacuolar-atpase In Sindbis Virus Imentioning
confidence: 99%
“…BAF has been used to inhibit VATPases from Neurospora crassa (4), Manduca sexta (55), yeast (53), and bovine chromaffin granules (14). It has also been used in cell culture with a variety of cell lines to look at infection with alphaviruses (12,27,46), flaviviruses (6,35,43), and other viruses (2,29). It has been used as a tool for inhibiting alphavirus infection, assuming alphaviruses use receptormediated endocytosis, followed by exposure to low pH to establish infection.…”
mentioning
confidence: 99%
“…Increasing evidence reveals that receptor-dependent endocytosis may be mediated by clathrin, which is regularly distributed over the cell surface (McMahon & Boucrot, 2011). In past decades, the entry of JEV into host cells, either mammalian or mosquito, was demonstrated to be significantly influenced by treatment with bafilomycin A1 (Andoh et al, 1998;Nawa, 1998). In fact, a number of flaviviruses like West Nile virus (Jiang et al, 2005), DENV (Acosta et al, 2008) and JEV (Chai et al, 2013), have been known to infect host cells via this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism for infecting host cells is also implemented by various mosquito-borne flaviviruses (Acosta et al, 2008;Chu & Ng, 2004). Among them the Japanese encephalitis virus (JEV), which infects host (either mammalian or mosquito) cells via receptor-mediated endocytosis (Andoh et al, 1998;Nawa, 1998), has also been confirmed to be clathrindependent (Chai et al, 2013;Yang et al, 2013), except for certain unusual cases (Kalia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%